Muon spin rotation study of the layered oxyselenide Sr2CoO2Ag2Se2 - Gill, GJW; Wilkinson, JM; Lang, F; Blandy, JN; Clarke, SJ; Blundell, SJ (American Physical Society, 2022)
The results of a muon spin rotation experiment on the layered oxyselenide Sr2CoO2Ag2Se2 are presented. The compound contains square-planar CoO2 layers and is found to exhibit a phase transition at 160.4(1) K to an antiferromagnetic configuration of the Co2+ ions. Density functional theory calculations were performed in order to determine the stopping site of the muon within the unit cell. The calculated magnetic dipole field at the muon stopping site was shown to be consistent with the proposed magnetic structure.